Electricity & direct water consumption on Irish pasture based dairy farms: A statistical analysis. (15th January 2018) - Shine, P.; Scully, T.; Upton, J.; Shalloo, L.; Murphy, M.D.
Highlights: 39.85 Wh and 7.43 l of water consumed per litre of milk produced. No cost savings due to milk cooling load shifting capabilities on day/night rate. Pre-cooling milk with ground water saved 21% milk cooling electricity consumption. Pre-cooling milk with ground water increased parlour water consumption by 41%. Water usage depends more upon farm processes than milk production and stock. Abstract: With the abolishment of the European Union milk quota system in April 2015, the Irish government has targeted a 50% increase in milk production by 2020 over 2007–09 levels. Resulting milk price volatility and environmental constraints are forcing farmers to produce milk at lower costs with a lower overall environmental footprint. This entails using less energy and water resources to maintain commercial competitiveness and to reduce the environmental consequences of the production. This paper presents a detailed analysis of electricity and direct water consumption of 58 pasture-based, Irish commercial dairy farms. Data was acquired through a remote monitoring system installed on each farm in 2014 alongside corresponding milk production, stock, infrastructural and managerial data. The results derived from the analysis of this data allow key drivers of both electricity and water consumption to be understood with the ultimate aim of generating data to develop footprint models, to achieve a reduction in electricity and water use and to improve the cost efficiency of Irish pasture based dairy farms. The analysis showed electricity use of 39.84 Wh Lm −1 and water use of 7.43 Lw  Lm −1 for the period Jan - Dec 2015. Dairy farm processes directly associated with milk production (milk harvesting and milk cooling) were responsible for 47% of overall electricity consumption. Milk cooling systems which utilised ice chiller units or ice bank milk tanks consumed 32% greater Wh Lm −1 for milk cooling compared with direct expansion milk tanks. This increase in consumption was met with a 25% decrease in day-time hours consumption due to their load shifting capabilities resulting in no difference in milk cooling related cost per Lm when under a day and night electricity tariff structure. Mean milk cooling electricity savings of 21% were achieved across farms with the incorporation of ground water through a plate heat exchanger for milk pre-cooling. However, in an open loop system, this resulted in a 41% increase in parlour water consumption. Electricity consumption was found to be largely associated with milk production, herd size (total dairy cows) and the number of lactating cows. Water consumption was found to be largely correlated with milk production and moderately correlated with herd size and the number of lactating cows. Decreased correlation strengths for water consumption compared to electricity suggests consumption is less dependent on milk production and stock numbers and more dependent on managerial processes, environmental conditions and farm infrastructure. Results and methodologies from this analysis will facilitate the development of adaptive predictive and optimisation methodologies for dairy farming electricity and water consumption.